Utilizing lesson study in teaching synthetic division for procedural fluency in a post-pandemic classroom - Jessa Christine Dedal Agsalon; Joy Meribeles Anore; Hanna Arnedo Salinas; Princess Pera Dipasupil; Minie Rose Caramoan Lapinid (Jurnal Infinity, 2023)
Rigid planning, implementation, and evaluation of the learning activities has proved crucial in reflective teaching practice, especially in collaboration through a lesson study. This study was conducted in the Philippine post-pandemic context with the aim of using lesson study to improve lesson delivery in a HyFlex classroom setup in teaching synthetic division for procedural fluency. Participants included four collaborating full-time teachers and an intact class of twenty-two online and seventeen in-person learners. Research instruments were a self-assessment tool, classroom observation, and a focus group discussion. Most students could perform synthetic division but some failed to achieve procedural fluency due to poor prior knowledge in performing operations on real numbers and arranging terms in descending order of degree, and inadequate understanding of the concepts behind the algorithm. These findings underscore the importance of striking a balance between procedural fluency and conceptual understanding in a lesson. The challenges in conducting lesson study were difficulty in scheduling and conducting online meetings. The challenges in implementing the research lesson were intermittent and weak internet connection, HyFlex learning classroom management, and getting students to express their mathematical ideas. On the basis of these findings, the research lesson is then revised and improved for future implementation.